Food vs. Fuel: Examining the Tradeoffs in the Allocation of Biomass Energy Sources to Domestic and Productive Uses in Ethiopia - Mekonnen, Dawit; Bryan, Elizabeth; Alemu, Tekie; Ringler, Claudia (2015)
By: Dawit Mekonnen, Elizabeth Bryan, TekieAlemu, and Claudia Ringler Presented by Elizabeth Bryan (e.bryan@cgiar.org) Poverty and Applied Micro Seminar The World Bank Wednesday, October 7, 2015